2022
DOI: 10.2217/fon-2021-0970
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of breast cancer presentation during the COVID-19 pandemic: results from a cohort study in the UK

Abstract: Background: This study aimed to explore the hypothesis that the stage of breast cancer at initial diagnosis in 2020 is more advanced compared with 2019. Methods: Tumor, node, metastasis and Union for International Cancer Control (UICC) stages of new breast cancer diagnoses at the Bucks Breast Unit from May to October 2019 and 2020 were reviewed. A p < 0.05 was considered significant. Results: Average UICC stage increased from 1a in 2019 to 2a in 2020 (p < 0.01). Excluding cancers detected through screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 18 publications
3
24
0
1
Order By: Relevance
“…Similarly, Dutch data on colorectal cancer found decreases in incidence, particularly for stage I tumours 34 . From the UK, a shift towards more advanced breast cancer stages was reported between May and October 2020 after a substantial drop from 43.8% to 9.2% screen‐detected cases compared to 2019 35 . Another study from the UK reported reductions in number of low‐stage cases of cervical cancer in the early phase of 2020, 36 while no difference in pathological stage of skin cancer was found in the autumn of 2020 (Oct‐Dec) when referral rates where back to normal levels 37 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, Dutch data on colorectal cancer found decreases in incidence, particularly for stage I tumours 34 . From the UK, a shift towards more advanced breast cancer stages was reported between May and October 2020 after a substantial drop from 43.8% to 9.2% screen‐detected cases compared to 2019 35 . Another study from the UK reported reductions in number of low‐stage cases of cervical cancer in the early phase of 2020, 36 while no difference in pathological stage of skin cancer was found in the autumn of 2020 (Oct‐Dec) when referral rates where back to normal levels 37 .…”
Section: Discussionmentioning
confidence: 93%
“… 34 From the UK, a shift towards more advanced breast cancer stages was reported between May and October 2020 after a substantial drop from 43.8% to 9.2% screen‐detected cases compared to 2019. 35 Another study from the UK reported reductions in number of low‐stage cases of cervical cancer in the early phase of 2020, 36 while no difference in pathological stage of skin cancer was found in the autumn of 2020 (Oct‐Dec) when referral rates where back to normal levels. 37 In Denmark, a recent study did not find any significant changes in stage distribution across seven major cancer sites between 2019 and 2020.…”
Section: Discussionmentioning
confidence: 99%
“…An initial 2451 citations were identified for title and abstract screening, of which 77 were eligible for inclusion ( Fig. 1 ) [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] ,…”
Section: Resultsmentioning
confidence: 99%
“…For cancer, emerging data suggest upstaged disease presentations and poorer one-year survival outcomes among patients with delayed cancer surgery. 20 Among patients awaiting elective surgery, such as joint arthroplasty or heart valve replacement, a worsening of their condition while waiting is likely to increase their physical and mental suffering and make future treatment technically challenging and less likely to succeed. 2,21 In addition, the impacts on patients waiting for minor procedures, for example revision of perianal seton, removal of metalwork, bunionectomy, etc.…”
mentioning
confidence: 99%
“…Unfortunately, the degree of morbidity associated with delayed surgery or undiagnosed surgical pathology is only beginning to be understood. For cancer, emerging data suggest upstaged disease presentations and poorer one-year survival outcomes among patients with delayed cancer surgery 20 . Among patients awaiting elective surgery, such as joint arthroplasty or heart valve replacement, a worsening of their condition while waiting is likely to increase their physical and mental suffering and make future treatment technically challenging and less likely to succeed 2 , 21 .…”
mentioning
confidence: 99%